Patronage democracy in the Philippines clans, clients, and competition in local elections - Calimbahin, Cleo Anne A.; Teehankee, Julio C. (Bughaw, 2022)
Patronage Democracy in the Philippines: Clans, Clients, and Competition in Local Elections demonstrates the persistence of political patronage in local power relations and electoral dynamics in the Philippines. Through ten case studies of political contests in various parts of the country during the 2016 and 2019 elections, it documents how patronage takes different forms and flows through clientelistic and clan networks that are very much alive in local politics. The case studies—covering the provinces of Isabela, Camarines Sur, Cebu, Iloilo, and Lanao del Norte, and the cities of Manila, Makati, Caloocan, Cebu, and Bacolod—also provide nuanced understandings of how patronage is strategically dispensed and transformed, especially across distinctive yet changing local political contexts. It is hoped that the volume, by mapping the shifts in patronage-driven electoral politics in the country, informs future engagements and reflections on genuine democratic reforms.-- Back cover.